Product Innovation as a Catalyst for International Expansion of MSMEs : An Analysis of the Indonesian Creative Sector - Khalikussabir Khalikussabir; Sudarmiatin Sudarmiatin (Jurnal bintang manajemen, 2024)
The creative sector in Indonesia has great potential for economic growth, but many Micro, Small, and Medium Enterprises (MSMEs) face challenges in adopting product innovation for international expansion. This study aims to analyse the role of product innovation, marketing strategy, and collaboration with creative industries in supporting the international expansion of MSMEs. The method used is Structural Equation Modeling (SEM) analysis with AMOS, involving 600 registered MSMEs in the creative sector. The results showed that product innovation, effective marketing strategies, and collaboration have a significant influence on the ability of MSMEs to enter the global market. The findings imply that an increased focus on innovation and the development of adaptive marketing strategies, as well as building strong collaboration with stakeholders, are critical to the successful international expansion of MSMEs in Indonesia.